Effects of stocking density on lightweight pig performance prior to marketing - Potter, M. L.; Bergstrom, J. R.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 336 finishing gilts (initially 258 lb) were used in a 21-d growth trial to evalu- ate the effects of increasing stocking density on performance of pigs classified in the slower-growing fraction of the pig population. Pens of gilts were blocked to minimize variation associated with barn location and the diet fed for the 14 d prior to the start of this trial. Within each block, pens of pigs were randomly allotted to treatments (6 pens per treatment). Treatments included stocking pens with 8, 12, 16, or 20 pigs per pen, allowing 22.5, 15.0, 11.3, and 9.0 ft2/pig, respectively. Pens were weighed and feed intake determined on d 0, 7, 14, and 21 to calculate ADG, ADFI, and F/G. Pigs were fed a common diet with the inclusion of 4.5 g/ton Ractopamine HCl (RAC) (Paylean; Elanco Animal Health, Greenfield, IN) for the duration of the trial. Overall, as the number of pigs per pen increased, ADG and ADFI decreased (ADG and ADFI: linear, P < 0.01; ADFI: quadratic, P = 0.01), but no differences were measured in F/G. These performance differences resulted in numeric differences in pig weights (8 pigs: 316.6 lb, 12 pigs: 308.8 lb, 16 pigs: 310.9 lb, and 20 pigs: 307.0 lb) on d 21. These data indicate that in this commercial finishing barn, finisher pig ADG and ADFI improved as the number of pigs in each pen decreased. These findings suggest that as pigs are held in barns for extra days to add weight, their growth rates may be affected by stocking density.
Keywords: Swine; Growth; Lightweight pig; Stocking density